Nasal Malignant Peripheral Nerve Sheath Tumor Resembling Cavernous Hemangioma: A Case Report - Mohammad Rizki Pratama; Nur Hayati; Herwinda Octavia (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Malignant peripheral nerve sheath tumor (MPNST) is a malignant, locally invasive tumor that originates from Schwann cells in the peripheral nerves, and has a high probability of metastasize. It accounts for 5-10% of all soft tissue sarcomas and has an incidence of 0.001% in the general population. Because of its rarity and lack of specificity, little is known about its imaging features, and reports on the nasal region are uncommon. Case Report: A 43-year-old woman with symptoms of nosebleed from her right nostril and had a tampon inserted for 4 days, but the bleeding persisted. No history of trauma. Physical examination is inconclusive. CT Angiography (CTA) shows a hypervascular mass in the right nasal cavity extending into the ethmoidal sinus, suggesting a cavernous hemangioma. The patient underwent mass extirpation surgery. Histopathological and histochemical examination of the removed tissue revealed a malignant peripheral nerve sheath tumor. The patient then underwent radiotherapy. An MRI evaluation revealed no residual tumor. Discussion: Malignant peripheral nerve sheath tumor (MPNST) is a rare soft tissue sarcoma. This tumor can be aggressive by infiltrating the surrounding tissue, including bone structures, in contrast to hemangiomas. Computed tomography is useful for locating the tumor, identifying infiltration, and planning treatment. Because this reported case was believed to be in the early phases of the illness, the lesion found in CTA has regular margins and well-defined boundaries, thus it is more appropriate for cavernous hemangioma. As a multi-parameter modality, MRI can provide a wealth of information on characterizing various components in tumors, thus is used for further investigation and post-treatment evaluation. Conclusion: Because of the overlapping radiographic features, distinguishing MPNST from other more prevalent tumors, such as cavernous hemangioma, is challenging. It is important for radiologists to consider MPNST as a differential diagnosis of masses in the nasal cavity.